Groundwater Fluoride Contamination in Balochistan, Pakistan: Health Risk and Regional Variability Analysis using HQ and NPI Indices - Arain, Ghulam Murtaza; Sattar, Nazia; Khatoon, Sumaira; Naseem, Sadaf; Badshah, Shakeel (Asian Journal of Chemistry, 2025)
Groundwater fluoride contamination in Balochistan, Pakistan, poses significant public health and socio-economic challenges. This study comprehensively assessed groundwater quality across 7 districts, including Quetta, Loralai, Sibi, Kachi Bolan, Sohbatpur, Jafarabad and Naseerabad, through 825 samples collected during 2022 and 2023. Parameters analyzed included fluoride (F–), total dissolved solids (TDS), electrical conductivity (EC) and pH. Advanced indices, including hazard quotient (HQ), fluoride concentration (CF), pollution index (PIF) and Nemerow Pollution Index (NPI), were used to evaluate risks for male and female population groups. The highest F– contamination was observed in Sibi (58% unsafe samples), followed by Loralai (20.2%), with contamination severity ranked as Sibi > Loralai > Sohbatpur > Kachi Bolan > Quetta > Jafarabad > Naseerabad. HQ analysis revealed children are significantly more vulnerable, with the highest HQ for children observed in Sohbatpur (mean: 1.128). The CF analysis showed minimal risk for infants (< 1 year) but higher exposure for children (1-8 years), particularly in Sibi (mean: 0.112 mg/L). The NPI findings classified Nasirabad as minimal risk (NPI: 0.859), while Sibi, Sohbatpur, Kachi Bolan and Loralai posed high risks (NPI: 1.33-1.50), whereas EC and TDS variability highlighted groundwater quality differences, with high salinity and TDS concentrations in Sohbatpur and Jafarabad indicating unsuitability for drinking.